2019
DOI: 10.21926/obm.icm.1903051
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Acupuncture as a Non-Pharmacological Treatment for Neonatal Abstinence Syndrome (NAS)

Abstract: Background: The incidence of Neonatal Abstinence Syndrome (NAS) has been on the rise over the past decade. There are many factors that have possibly contributed to this increase such as more mothers using illicit drugs and the overuse of opioid medication. This results in an increase in costs and resources for the healthcare system. Newborns with NAS might experience withdrawal symptoms that can cause pain, distress, and may potentially increase the risk of future health complications. It is therefore importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This is contrasted with the HWR class, in which 53.36% received both pharmacologic and non-pharmacologic intervention and 46.64% received a non-pharmacologic intervention alone. Class characteristics on intervention type are consistent with previous research suggesting that pharmacologic interventions (typically opioids) are used in more severe withdrawal cases involving higher symptom counts (Mangat et al, 2019). In the case of less severe or absent withdrawal symptoms, which may be more common in the LWR class, it is likely that non-pharmacologic interventions are used over pharmacologic interventions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is contrasted with the HWR class, in which 53.36% received both pharmacologic and non-pharmacologic intervention and 46.64% received a non-pharmacologic intervention alone. Class characteristics on intervention type are consistent with previous research suggesting that pharmacologic interventions (typically opioids) are used in more severe withdrawal cases involving higher symptom counts (Mangat et al, 2019). In the case of less severe or absent withdrawal symptoms, which may be more common in the LWR class, it is likely that non-pharmacologic interventions are used over pharmacologic interventions.…”
Section: Discussionsupporting
confidence: 83%
“…Typically, treatment of NAS begins with non-pharmacologic interventions such as breastfeeding (Welle-Strand et al, 2013), swaddling (Mangat et al, 2019), parent-infant rooming-in (Holmes et al, 2016), and low stimulation environments (i.e., dark, quiet rooms), which yield beneficial outcomes. While these interventions may be common among newborns (e.g., around 80% of newborns are breastfed at some point; CDC, 2022), they are particularly helpful in cases of NAS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 However laser acupuncture needs to be further studied because other studies have demonstrated contradictory results. 20…”
Section: Laser Acupuncturementioning
confidence: 99%